Avaliação da densidade mineral óssea em mulheres pré-menopausadas com tireoidite crônica autoimune - FRANCISCON, Priscila de Melo (2018)
Introduction: Calcitonin deficiency has been reported in chronic autoimmune thyroiditis (ACT). The imbalance of secretion and action of the hormones involved in homeostasis of calcium and phosphorus metabolism, including calcitonin, may alter the concentrations of bone mineral components, the coupled action of osteoblasts and osteoclasts that act on the processes of bone remodeling, leading to changes in bone mass, resulting in osteopenia / osteoporosis. Objective: to investigate changes in bone mass in women with ACT, presumably deficient in calcitonin. Methods: We selected 45 premenopausal women with ACT assisted in the thyroid outpatient clinic. Of these, 33 performed biochemical and hormonal exams to exclude comorbidities, to evaluate bone metabolism and densitometry (DXA, Lunar DPX GE Prodigy apparatus); 26 met the inclusion criteria compared to 26 healthy women (CG group) matched for age and body mass index (BMI). Statistical analysis was performed using the SPSS program. As all variables presented normality, for comparisons we used Student's t-test and Chi-square test and for the correlations Pearson test, with significance being p <0.05. Results: Age varied from 30.0 to 45.6 years.months (median ACT 37.11 and CG 35.3) and BMI was 25.8 ± 6.3 and 27.5 ± 5.6 kg/m² in ACT and CG respectively. Thyroid function proved to be adequate and calcium, phosphorus, magnesium, parathormone and vitamin D concentrations were normal in both groups. The bone mineral density in the standard areas of the spine and femur was normal and showed no difference between the two groups, correlating positively only with BMI. Conclusion: There was no alteration of bone mass in the ACT compared to healthy patients. The presumed deficiency of calcitonin inherent to this clinical condition does not result in osteopenia / osteoporosis.